Using the Delphi Method to Identify Risk Factors Contributing to Adverse Events in Residential Aged Care Facilities - Shi C; Zhang Y; Li C; Li P; Zhu H (Dove Medical Press, 2020)
Chunhong Shi,1 Yinhua Zhang,2 Chunyan Li,1 Pan Li,1 Haili Zhu3 1Nursing Department, XiangNan University, Chenzhou 423000, People’s Republic of China; 2Nursing Department, Hunan University of Chinese Medicine, Changsha 410208, People’s Republic of China; 3Nursing Department, Hunan Academy of Traditional Chinese Medicine Affiliated Hospital, Changsha, 410006, People’s Republic of ChinaCorrespondence: Yinhua Zhang Email zhangyinhua@126.comPurpose: This study aimed to identify risk factors associated with adverse events in residential aged care facilities in China.Patients and Methods: After compiling a list of risk factors for adverse events generated from in-depth interviews with managers of residential aged care facilities, a three-round Delphi method was used to reach consensus. The synthesized risk factors were presented on a Likert scale to the expert panelists three times to validate their responses.Results: The list identified 67 items as risk factors for adverse events, attached to four first-level indexes (ie, environmental facility, nursing staff, older adults’ characteristics, and management factors). The experts’ authority coefficient was 0.87. The positive coefficients were 82.76%, 91.67%, and 100%, and the coordination coefficients were 0.154, 0.297, and 0.313 in the first, second, and third rounds, respectively.Conclusion: Using a Delphi method, this study established a consensus on risk factors contributing to adverse events and developed a risk assessment grade for use in future aged care practice and research. The resulting list is useful in prioritizing risk-reduction activities and assessing intervention or education strategies for preventing adverse events in residential aged care facilities.Impact: This study fills the gap in risk identification in the Chinese residential aged care system to ensure provision of best-practice care to this vulnerable population. Nursing staff and management factors at the top of the list are not only the most common causes of adverse events but also the core elements in creating a secure and error-free environment. This list was intended to support predictive and prevention-oriented decision-making by managers and nursing supervisors to reduce preventable adverse events.Keywords: residential aged care facilities, Delphi survey, risk factors, Aged care, adverse events